Work-related stress, inability to relax after work and risk of adult asthma: a population-based cohort study - Loerbroks, Adrian; Gadinger, Michael Christian; Bosch, Jos A.; Stürmer, T.; Amelang, Manfred (Allergy, 2010)
There is an extensive literature linking stressful work conditions to adverse health outcomes. Notwithstanding, the relationship with asthma has not been examined, although various other measures of psychological stress have been associated with asthma. Therefore, we aimed to investigate the relation between work stress and asthma prevalence and incidence.
Gesehen am 29.03.2023